1980
DOI: 10.1002/aja.1001590402
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in prolactin and growth hormone cells in the hypophyses of white‐tailed deer (Odocoileus virginianus borealis) studied by light microscopic immunocytochemistry and radioimmunoassay

Abstract: Numerous investigators have shown a relationship between basal serum prolactin (PRL) levels and photoperiod in domestic ungulates, and we have shown recently that a similar seasonal baseline serum PRL profile exists in both sexes of a captive but free-breeding population of white-tailed deer. In order to localize and describe the distribution and possible seasonal changes of PRL and growth hormone (GH) cells in the adenohypophyses of deer, we have used antisera raised against ovine PRL and bovine GH and the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Moreover, the ultrastructure of lactotrope cells exhibits dynamic changes throughout the year in the ovine pituitary, with hypertrophy, increased cytoplasmic area, and increased rough endoplasmic reticulum and density of prolactin secretory granules during the long days of summer [13]. Similar ultrastructural changes in response to season were reported in another photoperiodic species, the white tail deer [15], [16]. Thus, although the gonadotrope population appears to be stable throughout the year in most species, seasonally regulated changes in the lactotrope population result in circannual alterations in the lactotrope/gonadotrope cell communication, which are modulated by gonadal feedback and are likely to affect the function of gonadotropes.…”
Section: Morphologic Associations Between the Gonadotropic And Lactotsupporting
confidence: 62%
“…Moreover, the ultrastructure of lactotrope cells exhibits dynamic changes throughout the year in the ovine pituitary, with hypertrophy, increased cytoplasmic area, and increased rough endoplasmic reticulum and density of prolactin secretory granules during the long days of summer [13]. Similar ultrastructural changes in response to season were reported in another photoperiodic species, the white tail deer [15], [16]. Thus, although the gonadotrope population appears to be stable throughout the year in most species, seasonally regulated changes in the lactotrope population result in circannual alterations in the lactotrope/gonadotrope cell communication, which are modulated by gonadal feedback and are likely to affect the function of gonadotropes.…”
Section: Morphologic Associations Between the Gonadotropic And Lactotsupporting
confidence: 62%
“…In addition, Mirarchi et al (1978) have recently described a seasonal profile of serum PRL levels in male white-tailed deer, and studies by Schulte et al (1980a) have shown that PRL levels peak during midsummer and are lowest during the winter in both sexes of a captive but free-breeding population of adult deer of the same species. Furthermore, our recent observations in this species have shown a marked seasonal variation in the volume density and size of immunoreactive pituitary PRL cells, which is well correlated with immunoassayable levels of PRL in the hypophyses of these same animals (Schulte et al, 1980b). Accordingly, in order further to characterize seasonal cytological changes in pituitary acidophils in deer, we have immunocytochemically identified PRL and GH cells in hypophyses collected from adult animals throughout the year, and we have described the ultrastructural changes observed in these cells.…”
mentioning
confidence: 52%
“…In animals, that are seasonal breeders such as the hamster (Turek et al, 1975;Simpson et al, 1982;Steger et al, 1982;Urbanski et al, 1990;Bittman et al, 1996) mole rat (Gottreich et al, 1995), and deer (Schulte et al, 1980), the synthesis and secretion of LH, FSH, PRL are reduced in non-breeding seasons compared with those in breeding seasons. Our morphometric data on the adenohypophysial cells of Japanese wood mice showed clear seasonal changes.…”
Section: Discussionmentioning
confidence: 99%